Tunable Amine‐Reactive Electrophiles for Selective Profiling of Lysine. (16th December 2021) - Tang, Kuei‐Chien; Cao, Jian; Boatner, Lisa M.; Li, Linwei; Farhi, Jonathan; Houk, Kendall N.; Spangle, Jennifer; Backus, Keriann M.; Raj, Monika
Abstract: Proteome profiling by activated esters identified >9000 ligandable lysines but they are limited as covalent inhibitors due to poor hydrolytic stability. Here we report our efforts to design and discover a new series of tunable amine‐reactive electrophiles (TAREs) for selective and robust labeling of lysine. The major challenges in developing selective probes for lysine are the high nucleophilicity of cysteines and poor hydrolytic stability. Our work circumvents these challenges by a unique design of the TAREs that form stable adducts with lysine and on reaction with cysteine generate another reactive electrophiles for lysine. We highlight that TAREs exhibit substantially high hydrolytic stability as compared to the activated esters and are non‐cytotoxic thus have the potential to act as covalent ligands. We applied these alternative TAREs for the intracellular labeling of proteins in different cell lines, and for the selective identification of lysines in the human proteome on a global scale. Abstract : Tunable and hydrolytically stable electrophiles are reported for the chemo‐selective labeling of lysine with mass sensitive probes. These tunable amine‐reactive electrophiles (TAREs) were used to label proteins in various subcellular compartments inside cells and for global identification of lysine in the human proteome.